The Application Of Talent Management Strategies In Sports Human Resources Development - Imron*, Fatkhul; Santosa, Teguh; Budiyono, Kodrad; Widodo, Zandra Dwanita (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Human resource management in sports has become a special concern as an organizational asset for the sustainability of the Petanque Association of Central Java Province. This asset needs to be strategically optimized and managed to ensure effective and efficient operation. Talent management is a key part of implementing interconnected strategies and systems to optimize the active and dynamic work environment in developing sports human resources management processes and norms. This article describes the application of talent management strategies as a process in developing sports human resources in the Petanque branch of Central Java Province. The study shows that talent management involves three stages: first, identifying sports human resources through talent management strategies; second, developing talent groups alongside other groups through talent management development; and finally, retaining talent. These three stages represent a cohesive process in applying talent management strategies to sports human resources in the Petanque of Central Java Province.